Documenting the terrestrial invertebrate fauna of Barrow Island, Western Australia - Callan, S.; Majer, Jonathan; Edwards, K.; Moro, D. (Blackwell Publishing Asia, 2011)
An intensive survey of terrestrial invertebrates was undertaken on Barrow Island, off the north-west coast of Western Australia, over a 5-year period from 2005 to 2009. The study was conducted as part of an environmental impact assessment for a liquefied natural gas (LNG) development on the island, with the aim of providing baseline information on invertebrates as a component of a future detection program in support of the island's quarantine system. The study used a standardised methodology for sampling a variety of undisturbed native vegetation communities, in addition to disturbed sites (vegetated and non-vegetated sites) across the island. Pre-eminent invertebrate taxonomists from Australia and overseas were engaged to assist with the identification of the various invertebrate orders collected. A total of 1873 species and morphospecies from 27 invertebrate orders were collected, 292 of which represented named species. A total of 321 families of invertebrates were represented in the collections. Samples taken during the same month in two consecutive years exhibited almost the same degree of difference as samples taken during the same year in the wet and the dry season. For ants, the fauna had greater affinity with the adjacent Pilbara than the Carnarvon basin Bioregion. In terms of sampling rigour and taxonomic coverage, this work represents one of the most intensive and comprehensive terrestrial invertebrate surveys presently undertaken in Australia.